TP6.2.13 A PEG insertion pathway for Motor Neurone Disease patients improves efficiency and patient outcomes. (28th October 2021) - Rossi, Benjamin; Salem, Rola; Andrews, Stuart; Bowling, Kirk
Abstract: Aims: Patients with Motor Neurone Disease (MND) often require a Percutaneous Endoscopic Gastrostomy (PEG) as a palliative procedure during the later stages of their illness, due to swallowing difficulties. More recently these are being inserted earlier before the inevitable decrease in nutritional intake and subsequent fall in albumin levels. This allows patients to eat food they enjoy rather than concentrating on maintaining intake. Insertion has traditionally been done with local anaesthetic and OGD, which can be difficult and traumatic. We propose a method of insertion using TIVA (Totally Intravenous Anaesthetic) in theatre with no intubation, performed by the surgical team, with a pathway including pre-operative anaesthetic assessment. Methods: Data was collected from all PEG insertions performed in theatre from 1/1/2011 to 1/9/2019. MND patients following our pathway were compared to all other indications for PEG insertions. Length of stay (LOS), 30-day re-admission rates, 30-day, 90-day and 1-year mortality were analysed. Results: 98 patients were identified. Median LOS was 3 days (mean 12.2) with a 3% 30-day mortality, 12.2% 90-day mortality and 34.7% 1-year mortality. In the MND group there were 27 patients. Median LOS was 2 days (mean 8.6) with a 7.4% (2 patients) 30-day mortality, which remained 7.4% at 90 days. There were 13 re-admissions (13.3%) overall compared to 0% in the MND group (p = 0.04 (Chi-squared test)). Conclusions: PEG insertion under TIVA for MND patients is safe. A set pathway for admission and pre/post-insertion care increases efficiency with reduced length of stay and improves patient outcomes with no re-admissions.